Projek Pakej Rangsangan Di Bukit Changgang, Selangor - Yahaya , Nurizan (Penerbit Universiti Sains Malaysia, 1994)
The objectives of the stimulation package project were to identify some selected educational materials to help enhance the mental development of children. It also tried to encourage parents to be involved in the development and education of the children. The stimulation packages consisted of boxes that contained educational materials, toys and games suitable for children under 12 years old.